Improving the quality of citric acid and calcium chloride marinated culled cow meat - Klinhom, P. (2017)
The objective of this research was to evaluate the effects of immersion marination with citric acid, calcium chloride and combined mixture of citric acid and calcium chloride solutions on Semimembranosus meat quality traits. Meat cuts obtained from culled cows were marinated with 0.05 M citric acid, 0.2 M calcium chloride or the combined mixture of these two compounds for 24 hr. Non- marinated meat served as control. Application of calcium chloride to the marination (either solely or in combination) improved water holding capacity (WHC) thus reduced cooking loss and shear force values. Meat marinated in citric acid solution showed high exudative during cooking and was not significantly different in shear force value compared to the unmarinated samples. Lightness was higher (paler) in all marinated meat samples. The a* values showed that marinated meat with citric acid solution had less red intensity. Lower of yellow intensity (b* value) appeared in the meat samples marinated with calcium chloride and the combined mixture. The sensory attribute evaluation showed that the highest scores for juiciness and tenderness were for calcium chloride and the combined mixture. The lowest flavor score was found in the meat marinated with citric acid solution and reported as sour. Sample treated with calcium chloride revealed no detrimental effect on meat flavor and odour. The evidence in the present study indicates that calcium chloride marinate solution increases juiciness and tenderness of meat from culled cow.